Consequences of ecological aggregation in general equilibrium analysis of perturbed ecosystems - Stephanie Brockmann; David C. Finnoff; Doran M. Mason; Edward S. Rutherford; Hongyan Zhang (Ecological Economics, 2024)

Valuing bioeconomic impacts of regulation on nutrient loads mediated by invasive mussels in Lake Michigan - Stephanie Brockmann; David Finnoff; Nicholas Boucher; Doran M. Mason; Edward S. Rutherford; Hongyan Zhang (Journal of Environmental Management, 2023)

Fish or not fish—fisheries participation and harvest diversification under economic and ecological change - Tobias Schwoerer; Kevin Berry; Darcy G. Dugan; David C. Finnoff; Molly Mayo; Jan Ohlberger; Eric J. Ward (Marine Policy, 2023)

Non‐stationary and interactive effects of climate and competition on pink salmon productivity - Jan Ohlberger; Eric J. Ward; Richard E. Brenner; Mary E. Hunsicker; Stormy B. Haught; David Finnoff; Michael A. Litzow; Tobias Schwoerer; Gregory T. Ruggerone; Claudine Hauri (Global Change Biology, 2022)
Pacific salmon ( Oncorhynchus spp.) are exposed to increased environmental change and multiple human stressors. To anticipate future impacts of global change and to improve sustainable resource management, it is critical to understand how wild salmon populations respond to stressors associated with human‐caused changes such as climate warming and ocean acidification, as well as competition in the ocean, which is intensified by the large‐scale production and release of hatchery reared salmon. Pink salmon ( O . gorbuscha ) are a keystone species in the North Pacific Ocean and support highly valuable commercial fisheries. We investigated the joint effects of changes in ocean conditions and salmon abundances on the productivity of wild pink salmon. Our analysis focused on Prince William Sound in Alaska, because the region accounts for ~50% of the global production of hatchery pink salmon with local hatcheries releasing 600–700 million pink salmon fry annually. Using 60 years of data on wild pink salmon abundances, hatchery releases, and ecological conditions in the ocean, we find evidence that hatchery pink salmon releases negatively affect wild pink salmon productivity, likely through competition between wild and hatchery juveniles in nearshore marine habitats. We find no evidence for effects of ocean acidification on pink salmon productivity. However, a change in the leading mode of North Pacific climate in 1988–1989 weakened the temperature–productivity relationship and altered the strength of intraspecific density dependence. Therefore, our results suggest non‐stationary (i.e., time varying) and interactive effects of ocean climate and competition on pink salmon productivity. Our findings further highlight the need for salmon management to consider potential adverse effects of large‐scale hatchery production within the context of ocean change.

Bioeconomics of invasive species: using real options theory to integrate ecology, economics, and risk management - Charles Sims; David Finnoff; Jason F. Shogren (Food Security, 2016)

Ship-borne Nonindigenous Species Diminish Great Lakes Ecosystem Services - John D. Rothlisberger; David C. Finnoff; Roger M. Cooke; David M. Lodge (Ecosystems, 2012)